2019
DOI: 10.33654/math.v5i2.604
|View full text |Cite
|
Sign up to set email alerts
|

The effect of academic and pedagogic competences on basic teaching skills of mathematics teacher candidates in micro teaching

Abstract: Keterampilan mengajar merupakan salah satu keterampilan dasar yang harus dikuasai oleh seorang guru. Oleh karenanya, mahasiswa calon guru perlu terus menerus melatih diri untuk mengembangkan keterampilan mengajarnya. Salah satu cara yang diusahakan adalah melalui pengajaran mikro pada mata kuliah PSAP (Perencanaan, Strategi, Asesmen, Pembelajaran) Matematika. Tujuan penelitian ini adalah untuk mengetahui kontribusi dari kemampuan akademik dan pedagogik mahasiswa calon guru terhadap keterampilan dasar mengajar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…SapIslamic educationle (2017) also found that pedagogical abilities directly influence that can improve teacher assessment performance. Other research results also state that pedagogical ability is strongly correlated with basic teaching abilities and skills (Dirgantoro, 2019). It is therefore natural that researcher, for example, Sakti, Hairunisya, and Sujai (2019) say that the teacher's ability to teach pedagogical competence greatly influences and determines the development of future education processes.…”
Section: Introductionmentioning
confidence: 99%
“…SapIslamic educationle (2017) also found that pedagogical abilities directly influence that can improve teacher assessment performance. Other research results also state that pedagogical ability is strongly correlated with basic teaching abilities and skills (Dirgantoro, 2019). It is therefore natural that researcher, for example, Sakti, Hairunisya, and Sujai (2019) say that the teacher's ability to teach pedagogical competence greatly influences and determines the development of future education processes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pre-service teachers need to continuously train to improve their teaching skills (Dirgantoro, 2019). However, at this point, different abilities and behaviours between individuals may become apparent.…”
Section: Introductionmentioning
confidence: 99%